Microbiota Manipulation: A Literature Review of Oral and Topical Probiotic Efficacy in Acne Vulgaris - Radyat Fachreza; Jeniffer Handiokho; Indah Rosidha; Agnes Amalia (Indonesian Journal of Global Health Research, 2025)
Acne Vulgaris (AV) is a chronic inflammatory skin condition affecting global population, especially adolescents and young adults. Recent study highlighted the potential role of probiotics in managing AV by controlling the gut-skin microbiome axis. Objective: This review aimed to examine the role of human microbiota in controlling AV and explore how probiotics can contribute to the prevention and treatment of AV. Methods: A literature search was conducted from multiple databases (Google Scholar, PubMed, Hindawi, Science Direct, Proquest, and Cochrane) from 2014 to 2024. The inclusion criteria is study written in English that focus on probiotics effects on AV, with a total of 1,435 articles early identified and 1,217 articles carefully screened. Results: Multiple studies showed the potential of both oral and topical probiotics in managing AV. Key findings include: Probiotics can inhibit bacteria that can cause acne like Cutibacterium acnes, some probiotic strains (e.g., Lactobacillus and Bifidobacterium) showed promising improvements in reducing inflammatory lesions, probiotics help controlling immune responses and reduce inflammation. Conclusion: Probiotics show promising potential as an alternative or additional treatment for AV by balancing gut and skin microbiomes. However, further research is needed to be explored to understand the molecular mechanisms and optimizing probiotic treatment strategies.